2011
DOI: 10.2355/isijinternational.51.1740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Texture on r-value of Ferritic Stainless Steel Sheets

Abstract: The effects of cold rolling texture on the formation of recrystallization texture and the relationship between recrystallization texture and r-value were investigated for sheets of titanium-stabilized extra-high purity Type 436L and Type 409L ferritic stainless steels. The recrystallization texture and average r-value were affected by the cold rolling texture. Annealed sheets with a sharp γ-fiber texture and very high average r-values were obtained from cold-rolled sheets with a strong γ-fiber texture (Type A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…[23][24][25][26][27][28] In a previous paper, 16) the authors illustrated that the texture of the α phase in Type 329J4L was dominant for the anisotropy of r-value. Furthermore, like a case of single-phase ferritic steels, 20,29) the r-values in Type 329J4L calculated from the texture of the α phase using the relaxed-constraints (RC) model with the RC1323 and a critical resolved shear stress (CRSS) ratio of 1.1 were in good agreement with the experimental values. 16) Here, the RC1323 model, i.e., the pancake version in which e13 and e23 (where 1, 2, and 3 are defined as the tensile, width, and thickness directions, respectively) were left free, and the CRSS ratio was the same as that for the {211} and {110} glide planes (τ c{211} /τ c{110} ).…”
Section: Effect Of Texture On Planar Anisotropysupporting
confidence: 70%
See 1 more Smart Citation
“…[23][24][25][26][27][28] In a previous paper, 16) the authors illustrated that the texture of the α phase in Type 329J4L was dominant for the anisotropy of r-value. Furthermore, like a case of single-phase ferritic steels, 20,29) the r-values in Type 329J4L calculated from the texture of the α phase using the relaxed-constraints (RC) model with the RC1323 and a critical resolved shear stress (CRSS) ratio of 1.1 were in good agreement with the experimental values. 16) Here, the RC1323 model, i.e., the pancake version in which e13 and e23 (where 1, 2, and 3 are defined as the tensile, width, and thickness directions, respectively) were left free, and the CRSS ratio was the same as that for the {211} and {110} glide planes (τ c{211} /τ c{110} ).…”
Section: Effect Of Texture On Planar Anisotropysupporting
confidence: 70%
“…1 and 6. Generally, high temperature annealing often improves the r-value in ferittic stainless steel sheets, 19,20) but the r-value in the DSS is different from that in a single α phase. The fraction of α phase increases with high temperature annealing in the case of DSS.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, some authors 17,28 have reported that θ-fiber is unfavorable when attempting to obtain a high r ̅ value. Hamada et al 12 demonstrated that the r ̅ value for the {100}〈011〉 and {100}〈001〉 orientations are notably low in almost all directions. The reduction of the θ-fiber fraction, from the 0.11 to 0.08, obtained with the addition of intermediate annealing improves the r ̅ value, and the γ/θ ratio reached approximately 5.25.…”
Section: Discussionmentioning
confidence: 99%
“…Yazawa et al 11 reported that the r ̅ value is related to the γ-fiber in the recrystallization texture. Furthermore, the enhancement and uniformity of the γ-fiber is essential in order to improve the r ̅ value [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation